Beachcast degradation stages of Rugulopteryx okamurae and Zostera noltii: towards a scalable remote-sensing monitoring platform - Mar Roca-Mora; Bede Ffinian Rowe Davies; Pierre Gernez; Maria Laura Zoffoli; Laurent Barillé (Remote Sensing Applications: Society and Environment, 2026)

Mapping the distribution of an intertidal invasive red macroalga at a national scale using satellite remote sensing - Bede Ffinian Rowe Davies; Simon Oiry; Mar Roca-Mora; Martin Gade; Valérie Stiger-Pouvreau; Anne-Laure Barillé; Anthony Le Bris; Pierre Gernez; Laurent Barillé (Remote Sensing Applications: Society and Environment, 2026)

Nutrient reduction scenarios cannot offset climate-driven habitat deterioration of Posidonia oceanica - Ana Azevedo; Elisa Garcia-Gorriz; Mar Roca-Mora; Diego Macias; Luca Polimene (Frontiers in Marine Science, 2026)
Seagrasses are marine plants and key indicators of water quality. Changes in environmental conditions may lead to seagrass deterioration with potential loss of associated ecosystem services (e.g., sediment accretion and stabilisation, carbon sequestration, habitat and food provisioning for important commercial and economic species of fish and invertebrates). In this study, we set up a habitat suitability model (MaxEnt) for Posidonia oceanica in the Mediterranean Sea to explore the interplay between shifts in environmental drivers, namely nutrients, and seagrass habitat suitability. We run the model for present and a future climate projection (RCP 4.5 scenario up to 2050). For future projections, we run three different nutrient input scenarios (business as usual – BAU – and two scenarios with reductions in riverine nitrogen and phosphorus loads). Results suggest that assuming full protection of P. oceanica suitable habitat, i.e., no anthropogenic pressures, it is expected a decrease of about 11% (due to climate change only) of suitable habitat area in relation to the estimated present suitable habitat area. However, by implementing upstream policy measures that reduce the nutrient input in the basin (a 6% reduction in Nitrogen load and a 3% reduction in Phosphorous load), this decrease is reduced to about 6% of suitable habitat area in comparison to the estimated area for present conditions. Under the ambitious nutrient reduction (less 21% of Nitrogen load and less 44% of Phosphorous load), projected losses in suitable habitat area were similar to those under the BAU scenario, with decreases of about 11% of suitable habitat area by 2050 in relation to the present estimations. These results suggest: i) a non-linear response of seagrass habitat to nutrient load reductions with benefits limited up to a certain (currently unquantified) threshold and ii) nutrient reduction policies targeting coastal eutrophication in the Mediterranean Sea, can only marginally offset climate-driven decline in P. oceanica habitat suitability. As such, additional conservation and climate-adaptation measures will likely be required to address projected climate-driven habitat suitability declines. Our results reinforce the vulnerability of P. oceanica meadows to a global changing environment and the need of complex and holistic transboundary management actions towards its recovery.

Trends and risk factors of antimicrobial resistance of Neisseria gonorrhoeae in Catalonia, Spain, 2022–2023 - Mercè Herrero; Sonia Broner; Naiana Pastrana-Batalla; Eduard Anfruns; Evelin López-Corbeto; Victoria González; Judit Serra-Pladevall; Nieves Larrosa; Jacobo Mendioroz; Pilar Ciruela; Yuliya Poliakova; Mateu Espasa; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Pollution and climate change trigger seagrass losses in the southwestern Atlantic - Carlos Eduardo Peixoto-Dias; Mar Roca-Mora; Manuel Vivanco Bercovich; Kalina Manabe Brauko; Alex Cabral; Marina Nasri Sissini; Bruna Rodrigues Moreira; Willian da Silva Oliveira; Hanna Brum François Amaral; Joel Christopher Creed; Paulo Horta (Marine Pollution Bulletin, 2026)

Unsupervised machine learning applied to Sentinel-2 time series for monitoring coastal lagoon water quality - Paola Barba-Ceballos; Sergio Heredia; Gabriel Navarro; Belén Rosado; Mar Roca-Mora; Isabel Caballero (Journal of Hydrology, 2026)

Blending PlanetScope and Sentinel-2 imagery to assess subtidal seagrass changes in turbid waters - Mar Roca-Mora; Carlos Eduardo Peixoto-Dias; Manuel Vivanco-Bercovich; Chengfa Benjamin Lee; Alessandra L. Fonseca; Isabel Caballero; Gabriel Navarro; Paulo Horta (Marine Pollution Bulletin, 2026)

An initial map of European intertidal seagrass - Bede Ffinian Rowe Davies; Simon Oiry; Mar Roca; Philippe Rosa; Maria Laura Zoffoli; Dimitris Poursanidis; Tobias Dolch; Bárbara Ondiviela; Cristina Galván; Ana C. Brito; Richard J. Lilley; Laura L. Govers; et al. (Remote Sensing of Environment, 2026)

Massive wastewater discharge severely impacts a whole eutrophic coastal lagoon ecosystem - Mar Roca; Carlos Eduardo Peixoto-Dias; Paulo Horta; Pablo Almaraz; Sergio Heredia; Isabel Caballero; Gabriel Navarro; Alessandra D. Fonseca (Marine Pollution Bulletin, 2025)

Exploring the mitigation of compound events in Barcelona: Urban water scarcity, flood risk and reduction of surface temperatures through water-sensitive urban design - María del Mar Pérez Cambra; Maria Dolors Martínez Santafé; Josep Roca Cladera (Urban Climate, 2025)

Rapid invasion and expansion of the invasive macroalgae Rugulopteryx okamurae in the Mediterranean and Atlantic: A 10-year review - Mohamed Rami Laamraoui; Bilal Mghili; Mar Roca; Olfa Chaieb; E. Ostalé-Valriberas; A. Martín-Zorrillae; A. Sabino-Lorenzo; Saida Aarab (Marine Pollution Bulletin, 2024)

Long-term bathymetric changes in the submerged delta of the Turia river since the nineteenth century (Western Mediterranean) and their drivers - Rafael Garcés; Mar Roca; Borja Martínez-Clavel; Ana M. Blázquez (Science of The Total Environment, 2023)

Monitoring the marine invasive alien species Rugulopteryx okamurae using unmanned aerial vehicles and satellites - Mar Roca; Martha Bonnet Dunbar; Alejandro Román; Isabel Caballero; Maria Laura Zoffoli; Pierre Gernez; Gabriel Navarro (Frontiers in Marine Science, 2022)
Rugulopteryx okamurae is a species of brown macroalgae belonging to the Dictyotaceae family and native to the north-western Pacific. As an Invasive Alien Species (IAS), it was first detected in the Strait of Gibraltar in 2015. Since then, R. okamurae has been spreading rapidly through the submerged euphotic zone, colonizing from 0 to 50 m depth and generating substantial economic and environmental impacts on the Andalusian coasts (southern Spain). More than 40% of marine IAS in the European Union (EU) are macroalgae, representing one of the main threats to biodiversity and ecosystem functioning in coastal habitats. This study presents a monitoring pilot of beached R. okamurae and fresh R. okamurae down to 5 m depth in Tarifa (Cadiz, Spain), combining multispectral remote sensing data collected by sensors on-board Unmanned Aerial Vehicles (UAVs) and satellites, and how this information can be used to support decision-making and policy. We used an UAV flight carried out at Bolonia beach (Tarifa, Spain) on 1 st July 2021 and Sentinel-2 (S2) and Landsat-8 (L8) image acquisitions close to the drone flight date. In situ data were also measured on the same date of the flight, and they were used to train the supervised classification Super Vector Machine (SVM) method based on the spectral information obtained for each substrate cover. The results obtained show how multispectral images allow the detection of beached R. okamurae , and the classification accuracy for water, land vegetation, sand and R. okamurae depending on the image resolution (8.3 cm/pixel for UAV flight, 10 m/pixel for S2 and 30 m/pixel for L8). While the UAV imagery precisely delimited the area occupied by this macroalgae, satellite data were capable of detecting its presence, and able to generate early warnings. This study demonstrates the usefulness of multispectral remote sensing techniques to be incorporated in continuous monitoring programmes of the marine IAS R. okamurae in coastal areas. This information is also key to supporting regional, national and European policies in order to adapt strategic management of invasive marine macrophytes.

A multidrug-resistant microorganism infection risk prediction model: development and validation in an emergency medicine population - Juan González del Castillo; Agustín Julián-Jiménez; Julio Javier Gamazo-Del Rio; Eric Jorge García-Lamberechts; Ferrán Llopis-Roca; Josep María Guardiola Tey; Mikel Martínez-Ortiz de Zarate; Carmen Navarro Bustos; Pascual Piñera Salmerón; Jesús Álvarez-Manzanares; María del Mar Ortega Romero; Martin Ruiz Grinspan; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)